Increasing antioxidant activity of soursop (Annona muricata L.) and noni (Morinda citrifolia L.) leaves fermented by Lactobacillus plantarum BP102 - Dayu Nirwana Putri; Sri Widyarti; Yoga Dwi Jatmiko (The East Java Biological Society, 2022)
Free radicals are constantly produced by either cell metabolism or from external sources. At high concentration, they induced a tissue damage called oxidative stress. Soursop leaf (Annona muricata L.) and noni leaf (Morinda citrifolia L.) are medicinal plants with potency as antioxidants. This study aimed to evaluate the capacity of Lactobacillus plantarum BP102 in elevating the antioxidant activity of soursop and noni leaves. Dried-powder and methanol extract of soursop and noni leaves were diluted with sterile distilled water 3 g/30 mL and 0.3 g/30 mL, respectively, inoculated with 1% (v/v) of L. plantarum BP102 inoculum. The antioxidant activity was carried out using the 2.2-diphenyl-1-picrylhydrazyl (DPPH) method. The antioxidant activity increased in dried-powder and methanol extract of soursop and noni leaves with different activity levels after being fermented using L. plantarum BP102 based on IC50. The increasing antioxidant activity in dried-powder of soursop leaves IC50 6.41±0.06 to 0.034±0.01 mg/mL (99.5%) was higher than of the methanol extract IC50 2.78±0.00 to 0.11±0.01 mg/mL (96%). Unfortunately, the effect of fermentation towards noni leaves could only be observed in the form of methanol extract IC50 12.8±0.01 to 0.33±0.02 mg/mL (increased by 97.4%), the dried-powder of noni leaves was suspended and produced a dark color. The probiotic L. plantarum BP102 was used as a fermented agent in increasing the bioactive compounds especially related to antioxidant activity.